Effects of Sensory Garments on Sleep of Children with Autism Spectrum Disorder - Lisa Mische Lawson; Lauren Foster; Morgan Hodges; Mia Murphy; Melissa O'Neal; Lesan Peters (Hindawi-Wiley, 2022)
Objective. The purpose of this study is to assess the effectiveness of the use of sensory garments for improving sleep in children with autism spectrum disorder. Method. Using a single-subject ABAB reversal design, the researchers evaluated the effectiveness of a sensory garment on sleep duration, sleep latency, and parental stress related to a child's sleep. Four children aged 4-10 participated. We measured sleep duration and sleep latency using the Garmin watches and parent-report sleep logs, parent stress using the Parenting Stress Index Short Form, and sleep behaviors using the Children's Sleep Habits Questionnaire. Results/Discussion. Data showed variable effects on sleep duration and latency across children. The oldest child with the hyposensitive sensory patterns experienced the greatest sleep improvements. All parents experienced stress from daily life, and some reported increased stress due to study participation. Future research is recommended to further investigate the effectiveness of sensory garments on sleep for children with ASD. Therapists are encouraged to evaluate children's development and sensory preferences prior to recommending sensory garments for sleep.